Desulfonation of Linear Alkylbenzenesulfonate Surfactants and Related Compounds by Bacteria - Kertesz, Michael A. (1994)
Pseudomonas putida S-313 (= DSM 6884) grew in sulfate-free medium when the sole sulfur source supplied was one of several arylsulfonates involved in the synthesis, application, or biodegradation of linear alkyl-benzenesulfonate (LAS) surfactants. 2-(4-Sulfophenyl)butyric acid, 4-n-butyl-1-methyl-6-sulfotetralin, and 4-toluenesulfonic acid were each completely utilized during growth, as were the model LAS 1-(4-sulfophenyl) octane and the arylsulfonate dyestuff Orange II. The product in each case was the corresponding phenol, which was identified by gas chromatography-mass spectrometry or (1)H nuclear magnetic resonance. Stoichiometric conversion of 4-toluenesulfonic acid to 4-cresol was observed. The molar growth yields observed were 2.4 to 2.8 kg of protein per mol of S, which were comparable to the yield for sulfate. Commercial LAS disappeared from growth medium inoculated with strain S-313, but negligible growth occurred; digestion of cells in alkali led to recovery of the LAS mixture, which seemingly sorbed to the cells. However, mixed culture L6 was readily obtained from batch enrichment cultures containing commercial LAS as a sole sulfur source and an inoculum from domestic sewage. Culture L6 desulfonated components of the LAS surfactant to the corresponding phenols, which were identified by gas chromatography-mass spectrometry. Compounds with shorter alkyl chains were desulfonated preferentially, as were the centrally substituted isomers. In the presence of 200 μM sulfate, culture L6 grew well and LAS disappeared, although this was due purely to sorption, as shown by digestion of the cells in alkali. Thus, under sulfate-limited conditions, LAS can be desulfonated directly.